New multiplex real-time PCR approach to detect gene mutations for spinal muscular atrophy. Issue 1 (December 2016) - Liu, Zhidai; Zhang, Penghui; He, Xiaoyan; Liu, Shan; Tang, Shi; Zhang, Rong; Wang, Xinbin; Tan, Junjie; Peng, Bin; Jiang, Li; Hong, Siqi; Zou, Lin
Abstract Background Spinal muscular atrophy (SMA) is the most common autosomal recessive disease in children, and the diagnosis is complicated and difficult, especially at early stage. Early diagnosis of SMA is able to improve the outcome of SMA patients. In our study, Real-time PCR was developed to measure the gene mutation or deletion of key genes for SMA and to further analyse genotype-phenotype correlation. Methods The multiple real-time PCR for detecting the mutations of survival of motor neuron (SMN ), apoptosis inhibitory protein (NAIP ) and general transcription factor IIH, polypeptide 2 gene (GTF2H2 ) was established and confirmed by DNA sequencing and multiplex ligation-dependent probe amplification (MLPA). The diagnosis and prognosis of 141 hospitalized children, 100 normal children and further 2000 cases of dry blood spot (DBS) samples were analysed by this multiple real-time PCR. Results The multiple real-time PCR was established and the accuracy of it to detect the mutations ofSMN, NAIP andGTF2H2 was at least 98.8 % comparing with DNA sequencing and MLPA. Among 141 limb movement disorders children, 75 cases were SMA. 71 cases of SMA (94.67 %) were withSMN c.840 mutation, 9 cases (12 %) withNAIP deletion and 3 cases (4 %) withGTF2H2 deletion. The multiple real-time PCR was able to diagnose and predict the prognosis of SMA patients. Simultaneously, the real-time PCR was applied to detect trace DNA from DBS and able to make an early diagnosis of SMA. Conclusion The clinical and molecular characteristics of SMA in Southwest of China were presented. Our work provides a novel way for detecting SMA in children by using real-time PCR and the potential usage in newborn screening for early diagnosis of SMA.